1998
DOI: 10.7589/0090-3558-34.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Mycoplasmal Conjunctivitis in House Finches

Abstract: Observations from a citizen-based survey were used to identify potential risk factors associated with mycoplasmal conjunctivitis (Mycoplasma gallisepticum) in eastern house finches (Carpodacus mexicanus). Between November 1994 and October 1996, 778 volunteers provided 7,224 monthly observations at residential bird feeding sites across an eight state region in the eastern USA. Information collected by questionnaires included health status of house finches and four sympatric passerine species, types and number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 3 publications
2
25
0
1
Order By: Relevance
“…Existing evidence is circumstantial: Hartup et al (1998) reported that the odds of observing a wild house finch with conjunctivitis were higher at sites with tube feeders than at sites without them (i.e. with platform feeders or food on the ground).…”
Section: Introductionmentioning
confidence: 97%
“…Existing evidence is circumstantial: Hartup et al (1998) reported that the odds of observing a wild house finch with conjunctivitis were higher at sites with tube feeders than at sites without them (i.e. with platform feeders or food on the ground).…”
Section: Introductionmentioning
confidence: 97%
“…The disease was caused by a previously undescribed strain (14) of M. gallisepticum, a pathogen of poultry with a worldwide distribution that was first described in North America in 1936 and that had not previously been considered a pathogen of wild passerines (15). This pathogen apparently also infects American goldfinch (Carduelis tristis), purple finch (Carpodacus purpureus), and house sparrow (Passer domesticus) (16), although at far lower rates than house finches. House finches naturally infected with M. gallisepticum and held in captivity with ad libitum food developed conjunctivitis within 2-4 weeks, lost weight rapidly, and many (17) or all (18) died.…”
mentioning
confidence: 99%
“…gallisepticum has been isolated from a variety of different avian species, including galliformes (Benčina et al, 2003), anseriformes (Ibrahim et al, 2000), psittaciformes (Bozeman et al, 1984), columbiformes (Benčina et al, 1987), passeriformes Hartup et al, 1998;Mikaelian et al, 2001) and birds of prey (Poveda et al, 1990a,b;Morishita et al, 1997). M. iowae, usually found in turkeys, has been isolated from a range of free-flying birds (Amin, 1977), geese (Lin et al, 1995), a yellow napped amazon (Amazona ochrocephala auropalliata) (Bozeman et al, 1984) and even an apple seed (Grau et al, 1991).…”
Section: Introductionmentioning
confidence: 99%